REINTERPRETASI KEKERASAN DALAM RUMAH TANGGA SEBAGAI ALASAN PERCERAIAN DALAM PERSPEKTIF MAQASHID SYARIAH DAN HUKUM NASIONAL INDONESIA - Luluk (USRAH: Jurnal Hukum Keluarga Islam, 2026)
This study examines the reinterpretation of domestic violence as a basis for divorce. This issue has grown more complex with advances in technology and the effects of globalization, which have contributed to a rise in domestic violence cases. Such acts stand in stark contrast to the principles of Islamic law and do not reflect the values upheld in Islam. The purpose of this research is to explore the reinterpretation of domestic violence through the lens of maqāṣid al-syarī‘ah and Indonesian national law. The method employed is normative juridical research using statutory and library research approaches. The findings show that psychological violence deserves the same level of attention as physical violence, given its impact on family life. The study therefore proposes a legal reinterpretation grounded in maqāṣid al-syarī‘ah to broaden the understanding of Islamic law regarding psychological violence as a violation of key objectives of the law, namely the protection of intellect (hifẓ al-‘aql), religion (hifẓ al-dīn), and life (hifẓ al-nafs). This reinterpretation is an important step to ensure that Islamic law can respond to the challenges of globalization and technological development while maintaining its commitment to justice.